Phase‐Transfer Exchange Lead Chalcogenide Colloidal Quantum Dots: Ink Preparation, Film Assembly, and Solar Cell Construction. Issue 2 (24th September 2021) - Yuan, Mohan; Wang, Xia; Chen, Xiao; He, Jungang; Li, Kanghua; Song, Boxiang; Hu, Huicheng; Gao, Liang; Lan, Xinzheng; Chen, Chao; Tang, Jiang
Abstract: Solution‐processed colloidal quantum dots (CQDs) are promising candidates for the third‐generation photovoltaics due to their low cost and spectral tunability. The development of CQD solar cells mainly relies on high‐quality CQD ink, smooth and dense film, and charge‐extraction‐favored device architectures. In particular, advances in the processing of CQDs are essential for high‐quality QD solids. The phase transfer exchange (PTE), in contrast with traditional solid‐state ligand exchange, has demonstrated to be the most promising approach for high‐quality QD solids in terms of charge transport and defect passivation. As a result, the efficiencies of Pb chalcogenide CQD solar cells have been rapidly improved to 14.0%. In this review, the development of the PTE method is briefly reviewed for lead chalcogenide CQD ink preparation, film assembly, and device construction. Particularly, the key roles of lead halides and additional additives are emphasized for defect passivation and charge transport improvement. In the end, several potential directions for future research are proposed. Abstract : Phase‐transfer exchange (PTE) method has been widely employed for colloidal quantum dot (CQD) ink preparation. However, there is no review about PTE method that has been reported until now. In this review, the development of lead chalcogenide CQD ink is summarized, the key factors for high‐quality ink preparation are highlighted, and several potential directions for future research are proposed.